1962
DOI: 10.1677/joe.0.0250299
|View full text |Cite
|
Sign up to set email alerts
|

The Augmented Insulin Tolerance Test for Detecting Insulin Resistance

Abstract: SUMMARY 1. An augmented insulin tolerance test and its normal response is described; after a standard preparation, 11·1 u. of soluble insulin/m.2 of body surface is injected intravenously, and the level of blood sugar followed for 2 hr. 2. The degree of insulin resistance, in such states as acromegaly, can be indexed by the sum of the blood sugar values, as mg./100 ml., at 60, 90 and 120 min. after insulin. In normal subjects the mean 'insulin resistance index' was 92 (range 62–142). The test i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

1966
1966
1999
1999

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…Thus patients with acromegaly have been shown to be resistant to the hypoglycemic action of insulin (17); the four patients with untreated acromegaly in the present study required 0.30 U of insulin per kg to produce a response similar to that found in control subjects given half this amount. The increased insulin sensitivity found in hypopituitarism (18) or hypothalamic dysfunction (19) would appear to be of less diagnostic value, since some patients in the present study, who had definite endocrine hypofunction, showed a normal plasma sugar response to insulin.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Thus patients with acromegaly have been shown to be resistant to the hypoglycemic action of insulin (17); the four patients with untreated acromegaly in the present study required 0.30 U of insulin per kg to produce a response similar to that found in control subjects given half this amount. The increased insulin sensitivity found in hypopituitarism (18) or hypothalamic dysfunction (19) would appear to be of less diagnostic value, since some patients in the present study, who had definite endocrine hypofunction, showed a normal plasma sugar response to insulin.…”
supporting
confidence: 61%
“…Thus Patients 5, 6,12,13,14,17,19,21,22, and 24 were receiving 0.2 or 0.3 mg of L-thyroxine daily, Patients 5,6,12,14,19,21, and 22 were receiving 20 or 30 mg of cortisol daily, and Patient 27 was receiving 15 mg daily of methyl testosterone.…”
mentioning
confidence: 99%
“…Pregnancy is associated with an antagonism to the hypoglycemic action of insulin (3,4) which is comparable to that observed in acromegaly (5,6) and to that which follows the administration of growth hormone (7,8). Experimental studies have indicated that HPL, like growth hormone, induces impaired glucose tolerance in cortisol-treated hypophysectomized rats (9), stimulates glucose oxidation to CO2 and incorporation into fat in the rat epididymal fat pad (10), and promotes lipolysis in isolated fat cells ( 11 ).…”
Section: Introductionmentioning
confidence: 79%
“…There is evidence that glucocorticoids and growth hormone play an important role as hormonal insulin antagonists. Thus both Addison's disease and hypopituitarism are known to be associated with increased insulin sensitivity, whereas patients with Cushing's syndrome or acromegaly are resistant to its hypoglycemic action (2,3). The observation that the intravenous injection of insulin into control subjects results in rapid elevations of plasma cortisol (4,5) and growth hormone (6)(7)(8)(9) also supports the possible physiologic importance of these hormones as insulin antagonists.…”
mentioning
confidence: 99%